The Definitive Guide to SUSE Linux Enterprise Server 12 - Vugt, Sander van.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2014)
The Definitive Guide to SUSE Linux Enterprise Server 12 is a task-oriented book designed for self-study as well as classroom environments, which will also serve you as a reference guide. The book covers all skills that system administrators typically need to posses to administer SUSE Linux Enterprise Server in corporate environments. It starts at the beginning, which makes The Definitive Guide to SUSE Linux Enterprise Server 12 suitable for people without any preliminary Linux knowledge, and yet works up to advanced SUSE Linux administration tasks, such as building a cluster, optimizing performance or managing SUSE Linux Enterprise Server with SUSE Manager. The Definitive Guide to SUSE Linux Enterprise Server 12 is an ideal reference guide for system administrators, but is also perfect as a study book to prepare for the CLA, CLP as well as the CLE exams. This book contains step-by-step exercises, and scenario based exercises at the end of each chapter to help readers getting familiar with the subjects that are required to pass these three exams. The Definitive Guide to SUSE Linux Enterprise Server 12also contains test exams, so you can use it as a study guide in a formal learning environment or as a book that you can learn and test your own progress as you master SUSE Linux Enterprise Server. You'll learn everything you need to know and the skills you need to manage SUSE Linux Enterprise Servers, from installing a secure server, to performing the day-to-day management tasks on SUSE Linux Enterprise Server. Along the way you'll encounter and master SUSE Linux Enterprise Server in a data center environment, how to manage your SUSE Enterprise Server for High Availability, and you'll see how to manage your SUSE Linux Enterprise Server with SUSE Manager. From installation to expert management, The Definitive Guide to SUSE Linux Enterprise Server 12 will show you the ways to succeed with Linux Enterprise Server 12.
Keywords: Computer science; Computer Science; Computer Science, general; Electronic books